1996
DOI: 10.1001/archinte.1996.00440070085010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Hospital-Based Physicians and Trainees About HIV Infection in the United States, Canada, India, and Thailand

Abstract: Level of comfort in caring for HIV-infected patients and HIV/AIDS knowledge scores varied directly with the amount of previous contact with these patients. Disturbing numbers of health care professionals from all four countries did not understand the potential problems of the enzyme-linked immunosorbent assay serologic test and a significant percentage were unaware of the asymptomatic stage of HIV infection. There is a universal need for increased education of health care professionals about HIV infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The data in the current study support the assertion that the more the contact with PLWA, and the higher the knowledge base of these workers, the more willing the staff would be to offer care. This finding is similar to results from previous work by Brachman et al (30) which showed that the level of comfort in caring for HIV-infected patients and HIV/AIDS knowledge scores varied directly with the amount of previous contact with these patients.…”
Section: Discussionsupporting
confidence: 91%
“…The data in the current study support the assertion that the more the contact with PLWA, and the higher the knowledge base of these workers, the more willing the staff would be to offer care. This finding is similar to results from previous work by Brachman et al (30) which showed that the level of comfort in caring for HIV-infected patients and HIV/AIDS knowledge scores varied directly with the amount of previous contact with these patients.…”
Section: Discussionsupporting
confidence: 91%
“…Most literature supports that even though there may be specific areas of strength, there are gaps of HIV knowledge in: general populations [11], medical students [12,13], and healthcare workers [9,14-17]. Comparing knowledge levels between different studies has some limitations due to different questionnaire designs, but some comparisons are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-cultural studies of the psychological processes triggered by HIV infection suggest that people of different backgrounds cope with HIV and AIDS according to their own social mores and cultural traditions. As illustrated in a comparative analysis of health care providers in the United States, Canada, India, and Thailand (Brachman et al, 1996), health professionals in some locales have a limited knowledge of HIV diagnostic issues and have little experience working with patients with HIV and AIDS. The cultural context of those infected (as well as of the providers) must be addressed in order to improve both prevention and treatment efforts.…”
Section: Psychology Of Hivmentioning
confidence: 99%